REGULATION OF DIGITAL TRANSFORMATION PROCESSES OF REGIONAL ECONOMIC SYSTEMS - DERHALIUK, Marta (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article presents the principles of regulating the processes of digital transformation of regional economic systems. It was established that digitalization is considered as the introduction of various technologies into all spheres of social development. But to a greater extent, digital transformation is the key to development. Digital transformation is considered as the transformation of heterogeneous economic processes due to the introduction of new business models, strategies, systems, approaches and other tools due to the use of digital technologies. The use of digital technologies provides an opportunity to introduce new innovative, creative tools in various spheres of social development, as well as to increase the efficiency of the functioning of established processes. It is substantiated that the digitalization of regional economic systems occupies an important place in the development of regions, improving the quality of life of the population in all territories and increasing the level of economic security of the development of economic entities, the activation of international cooperation, etc. Digitization also plays an important role in ensuring the decentralization of power and the performance of functions that are delegated to localities. The main normative legal acts regarding the provision of processes of digital transformation of the regions of Ukraine have been studied. The positive consequences of the digital transformation of regional economic systems are singled out, which include: ensuring the speed of information transmission, its exchange, storage and processing; increasing the efficiency of management through the introduction of digital technologies; increasing the level of meeting the needs of consumers based on the timely determination of their requests; ensuring integration processes at different levels; facilitating access to services in the healthcare, education, and financial services system; overcoming corruption and increasing the transparency and efficiency of work of state and local authorities, etc.